Structural model of hassles experienced at travel destinations. (September 2018) - Lin, Wei-Rong
Abstract: Visitors expect to have pleasant experiences at travel destinations. However, they are often perplexed by hassles. Previous studies have rarely focused on the possible consequences of hassles experienced by visitors. Therefore, the present study constructed a complete hassle experience model for destinations, addressing the relationship between hassles and their consequences. A self-administered questionnaire was designed to collect empirical data from visitors to the Sun Moon Lake National Scenic Area in Taiwan. The results revealed that the visitors who experienced more hassles had stronger negative affect, and lower satisfaction and loyalty. Moreover, negative affect negatively influenced satisfaction, which subsequently influenced loyalty. The study then proposes several managerial implications based on these findings, discusses the research limitations, and makes suggestions for future studies. Highlights: Considers the relationship between hassle experience, negative affect, satisfaction, and loyalty. Hassle at destinations has a positive influence on negative affect. Hassle at destinations has a negative influence on satisfaction and loyalty. Expands the understanding of hassle experiences in tourist destinations.